Rotation of a Stealth CME on 2012 October 5 Observed in the Inner Heliosphere - Kumar, Sandeep; Hegde, Dinesha V.; Srivastava, Nandita; Pogorelov, Nikolai V.; Gopalswamy, Nat; Yashiro, Seiji (The Astrophysical journal, 2023)
Coronal mass ejections (CMEs) are subject to changes in their direction of propagation, tilt, and other properties. This is because CMEs interact with the ambient solar wind and other large-scale magnetic field structures. In this work, we report on the observations of the 2012 October 5 stealth CME using coronagraphic and heliospheric images. We find clear evidence of a continuous rotation of the CME, i.e., an increase in the tilt angle, estimated using the graduated cylindrical shell (GCS) reconstruction at different heliocentric distances, up to 58 R ⊙ . We find a further increase in the tilt at L1 estimated from the toroidal and cylindrical flux rope fitting on the in situ observations of interplanetary magnetic field (IMF) and solar wind parameters. This study highlights the importance of observations of Heliospheric Imager (HI), on board the Solar Terrestrial Relations Observatory. In particular, the GCS reconstruction of CMEs in the HI field of view promises to bridge the gap between the near-Sun and in situ observations at the L1. The changes in the CME tilt have significant implications for the space weather impact of stealth CMEs.